Answer:
64
Step-by-step explanation:
divide 2048 by 2 since half is already used gives you 1024 ...then divide 1024 by 16 to get 64..
-2(x - 5) + 4(9 + x)
-2x + 10 + 36 + 4x
=2x + 46
Answer:
the answer is a b and d
Step-by-step explanation:
I took the quiz
Answer:
Step-by-step explanation:a = m + (p-1)*d
b = m + (q-1)*d
c = m + (r-1)*d
p(b-c) = p*(q-r)*d
q(c-a) = q*(r-p)*d
r(a-b) = r*(p-q)*d
p(b-c)+q(c-a)+r(a-b)
= p*(q-r)*d + q*(r-p)*d +r*(p-q)*d
= (pq-pr+qr-pq+rp-qr)*d
= 0*d = 0
So i prove p(b-c)+q(c-a)+r(a-b)=0 hope this is helpfull